Components and potential utilization of oil sands semicoke. Issue 16 (17th August 2016) - Han, Xiangxin; Chen, Bin; Jiang, Xiumin
ABSTRACT: Retorting is one of the above-ground methods available for producing oil from oil sands, which also releases solid wastes such as oil sand semicoke. Although some oil sand retorting technologies have been explored and developed, such as rotary kilns and fluidized beds (FBs), there is little information on the components of their semicoke. Considering the semicoke to be a potential hazardous waste, this work first prepared the semicoke from retorting Indonesian oil sands, and then analyzed its components using different techniques, such gas chromatograph–mass spectrometer and X-ray diffractometer (XRD). The obtained results reveal that semicoke is a combustible fuel with a major proportion of toxic aromatic hydrocarbons and calcite. Based on the studies on the components of the semicoke and the characteristics of the FB retorting technology, a new oil sand utilization system with dual FBs is finally recommended for retorting oil sands in one fluidized bed and burning the semicoke in the other one.